Pelatihan Merakit dan Instalasi Laptop/Komputer pada Santri Yayasan Pendidikan Islam Pondok Pesantren Wali Songo Banjarbaru - Tri Wahyu Qur'ana; Al Fath Riza Kholdani; Hayati Noor (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2020)
Assembling a computer is a stage of bringing together the components needed to run correctly. To understand the correct computer assembly process, an understanding of computer hardware is required both logically and physically. Meanwhile, so that the computer can be operated according to its function, it is necessary to install it. Computer installation is installing a program (software) into a computer. All software (e.g., Microsoft Windows, Microsoft Office, and others) apart from that, also install functions to match the program with the tools installed on the computer and parse the compressed files. The expertise in assembling and installing laptops/computers can make a creative economy business field based on information technology. The Islamic Education Foundation of Wali Songo Islamic Boarding School is an Islamic religious, educational institution. Santri, as the nation's next-generation youth, needs to understand and have skills in assembling and installing laptops/computers, not only as passive users but also being active, the other side can also be used as part of driving the creative economy.